Pengaruh Penempatan, Lingkungan, Karakteristik Pekerjaan Terhadap Kinerja Menggunakan Variabel Intervening Kepuasan Kerja - Tontou, Agustina M (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
This study aims to examine the influence of job placement, work environment, job characteristics on performance with job satisfaction as intervening variable. Hypothesis can be concluded that job placement, work environment, job characteristics, and job satisfaction influence performance at PT. Hasjrat Abadi Manado partially and simultaneously. Primary data is used through questionnaire to as many as 62 employees of PT. Hasjrat Abadi Manado. Data analysis is path analysis. The result shows that the influence of job placement (X1), work environment (X2), job characteristics (X3) on job satisfaction (X4) simultaneously has contributed to job satisfaction (X4) as much as 38.0%. Variables of job placement (X1), work environment (X2), job characteristics (X3), and job satisfaction (X4) to employee performance (Y) used simultaneously to test the influence at 0.05% level of significance